Aquaporins - Hohmann, Stefan, 1956-; Nielsen, Sren, 1962-; Agre, Peter, 1949- (Current topics in membranes, 2001)
Aquaporins summarizes the present knowledge in this expanding field of research, starting with the structural analysis of water channel proteins. Subsequent chapters begin with mammalian aquaporins, examining physiology and pathophysiology, analysis of knock-out model animals, and the regulation of aquaporin function. Also covered is the distribution and regulation of aquaporins in plants and the function of water and glycerol channels in microbial systems.